Photovoltaic waste assessment in india and its environmental impact. Issue 1 (March 2021) - Sheoran, Manisha; Kumar, Pancham; Sharma, Susheela; Soni, Amit; Sahariya, Jagrati
Abstract: An increased energy demand of the world is met by the renewable sources of energy. In this solar photovoltaic technology has turned out as a major contributor. In India solar photovoltaic sector has enhanced from 1 GW to 28 GW from 2012 to 2018 and reached 32.627 GW on 30 March 2020 as reported by the MNERA. With the soaring installations, solar photovoltaic waste has also been increasing. 200, 000 million tonne of waste solar photovoltaic will be assembled in India till 2030 and approximately 1.8 million tonne by 2050. Solar photovoltaic technology includes crystalline silicon panels, amorphous silicon panels, CdTe, CIGS, GaAs panels. Among these crystalline silicon panels are used in India on a larger scale upto 93% . Life cycle assessment methodology is utilised. Environmental effects of c-Si, a-Si, CdTe, GaAS, CIGS on public health are assessed. Major health effects pertaining to different human body organs are also mentioned. The article also targets apparently thriving social, economic influence of the recycled solar photovoltaic panels. Interest of the society and recycling companies is also mentioned in the paper to highlight economic benefits that can be availed from the end life of the photovoltaic panels.